The importance of bee cultivation for humanity – bibliographic research from the perspective of the movie Bee Movie - Lima Neto, Inácio Alves de (Brazilian Journal of Production Engineering, 2025)
Bees perform important functions for nature; The most important is the pollination of flowers, which contributes to the perpetuation of the species, contributing to the production of fruits and vegetables that will serve as food for animals and humans. Due to numerous factors, it is noticed that the number of bee colonies has been decreasing over the years. The 2007 Dreamwoks animation Bee Movie promotes a discussion about the importance of bees for the entire planet Earth, so that, without them, all of humanity could disappear. From this perspective, a bibliographic research was carried out discussing the importance of bees for the ecosystem. It was concluded that the vision of the Bee Movie is current where it should, seeing the importance of these animals, promote actions of awareness and preservation of bee colonies.
Keywords: Bees; Importance; Preservation